TAJDĪD MAFHŪM AL-MĀ AL-MUṬLAQ FĪ AL-SIYĀQ AL-MU’ĀṢIR (DIRĀSAH MUQĀRANAH BAINA FUQĀHA AL-MAẒĀHIB WA AL-MU’ĀSHIR FI ḌAUI AL-TAṬHĪR BI AL-ISTIHĀLAH) - Razak Abdullah, Abdul; Munir, Badrul; M. Bennani, Abdelkarim (Islam Futura, 2022)
The development of science and technology at the present time in the treatment of water has affected the understanding of the meaning of water and the provisions of its use in jurisprudence, which led to a change in the meaning of absolute, pure and purified water. If the mazhab scholars discuss the status of water that consists of absolute water, used water, mixed water and impure water without any expansion of the return of the water status to the absolute state through unnatural processes, then contemporary scholars seek to expand the status of water to become absolute, pure and purified by an unnatural process. This research uses the library studies method with a comparison between the mazhab scholars and contemporary scholars in understanding absolute water, and uses an analytical framework based on the theory of Istihālah in the process of recycling or distilling water. The results of the study indicate that there are efforts to renew and expand the form of absolute water by contemporary scholars through the process of Istihālah, so that the water that was used, or impure water, sewage or waste, becomes absolutely pure and purified water again, if it goes through a hydrological process. The renewal and expansion of the meaning of the absolute is a creative effort and a kind of contemporary jurisprudence that goes in line with the spirit that jurisprudential rulings are constantly evolving within the framework of accommodating the development of science and technology.